The role of peers and the recreational environment in adolescent emotional safety. Issue 6 (2nd November 2022) - Wong, Janet B.; McDonough, Meghan H.; Bridel, William; Culos-Reed, Nicole
ABSTRACT: Emotional safety is important for facilitating positive outcomes in afterschool programmes. Emotional safety is not clearly conceptualised, and participants' understandings of, and experiences with how the social and built environment contribute to emotional safety in afterschool programmes is not well established. This qualitative case study examined early and middle adolescents' experiences with their peers and the programme environment, and how those experiences contributed to their feelings of emotional safety, from the perspective of both youth and staff working in afterschool recreational programmes. Ten adolescents between the ages of 11 and 15 along with 10 staff at two afterschool programmes in low-income urban neighbourhoods were interviewed. Data were analysed using thematic analysis. Adolescents described emotional safety as being understood and not feeling like they had to hide their authentic selves. Youth felt emotionally safe among trusted peers and staff who would protect them, when they felt free and had choices, and when they were in spaces where they felt comfortable. Findings have implications for youth afterschool programming and among staff who work with youth.